PMO-067 A response to NCEPOD (national clinical enquiry into patient outcome and death 2010) report—practice in provision of parenteral nutrition (PN) in a regional referral centre. (28th May 2012) - Hamid, N; Rochford, A; Soo, L; Barret, L; Grasso, N; Ali, R; Rahman, F; Forbes, A
Abstract : Introduction: The externally peer-reviewed NCEPOD report into the provision of PN alarmingly identified suboptimal care in 81% of patients receiving PN. We audited the quality of care received by parentally fed patients at a specialist regional centre for intestinal failure and home parenteral nutrition. Methods: Data were collected retrospectively for 100 inpatients seen between April and December 2011 on an NCEPOD modified audit tool; case notes were reviewed. Type I and II intestinal failure patients were included; home parenteral nutrition patients were excluded from the study. Results: Mean number of days patients were fed on PN was 12.2 (NCEPOD 13.2) and the range was 1–276 days (NCEPOD 1-212). 10% of patients were fed for 3 days or less (NCEPOD 10%) and 93% were fed for 30 days or less (NCEPOD 61%). The top two specialities referring patients were Colorectal 27% and Oncology 18% as compared to 22% from general surgery and 20% started in ICU in NCEPOD report. 12% referrals were deemed inappropriate and not started PN (NCEPOD 15%). Conclusion: Our hospital is a regional centre for intestinal failure and PN is prescribed exclusively through the nutrition support team (NST). Thus in comparison with the NCEPOD findings, the PN service at UCLH is of a high standard. Data collection were sufficient for direct comparison with most NCEPOD report parameters. The NST appeared to prevent inappropriate use of PN by not starting 12% of referred patients. Although a similar proportion of our patients (10%) were fed for 3 days or less as found in the NCEPOD report, half of these patients were commenced on TPN in ICU. We found much lower rates of PN-related metabolic and catheter-related complications compared with the NCEPOD report because of active NST monitoring and good quality nursing care. Retrospective data collection on IV fluid prescribing was not possible, but it was perceived that there was some inappropriate use of IV fluids. A comprehensive database is being developed to enable prospective data collection to evaluate and develop the service further. Competing interests: None declared. Reference: 1. NCEPOD . A Mixed Bag: The 2010 Report of the National Confidential Enquiry into Parenteral Nutrition . London: NCEPOD, 2010.